(untitled) (Research, Society and Development, 2021)
Zika is a self-limited febrile disease transmitted to man through the bite of an Aedes mosquito, mainly Aedes aegypti infected, or through vertical transmission from the infected mother to the fetus or newborn at the time of delivery. The biggest concern in the occurrence of Zika virus infection is the impairment of pregnant women due to fetal complications resulting from the infection. This study aimed to identify through bibliographic findings the main complications in newborns affected by microcephaly associated with Zika, the justification of this study is the need to identify which complications microcephaly leads to the lives of newborns affected by the disease. This is an integrative literature review research with a qualitative approach on the implications of Zika virus infection in newborns, with emphasis on microcephaly. The articles included in this study showed that the most significant changes in newborns with microcephaly are head circumference and delay in psychomotor development, the latter being an obstacle often experienced by the family as well. This study made it possible to identify marital complications resulting from the arrival of a newborn with microcephaly, and the difficulty of nursing professionals in dealing with the process of identification, surveillance and diagnosis. Among the complications for the newborn, it could be observed that neurological and psychomotor alterations are the most significant and require more attention.